The Position of Indigenous Knowledge in Canadian Co-management Organizations - Spak, Stella (Anthropologica, 2022)
Northern Canada has seen the emergence of various forms of resource co-management agreements over the last decades. Co-management arrangements either result from land-claim agreements between First Nations/Inuit, or crises (real or perceived) regarding a particular resource. Co-management organizations consisting of Indigenous and government representatives often claim to base their natural resource management decision-making on both biological resource science and the represented Indigenous peoples’ knowledge. This paper examines the actual ability of Canadian natural resource co-management boards to learn from the Indigenous Knowledge of represented First Nations communities. It will explore how the epistemological frameworks and employment structures within which co-management boards in Canada operate, shape the boards relationship to Indigenous knowledge. In particular the paper will examine the effect of power on the position of Indigenous Knowledge vis-a-vis biological resource science in the Canadian co-management arena.